(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Citrus fruits characterized by flavonoids and limonoids (terpenes) with the juice contains a high quantity of citric acid and sharp flavor. The study aimed to investigate the effect of Citrus Medicus extract on the histo-hepatic architecture and blood glucose parameters in Alloxan induced diabetic wistar rats. A total of Twenty (20) Wistar rats weighing between 75g-120g were used and were classified as control, normoglycemic, hyperglycemic without treatment with Citrus Medicus and hyperglycemic treated with Citrus Medicus. Hyperglycemia was induced with single dose of intraperitoneal injection of Alloxan at 120 mg/kg. Administration was carried for 42 days experimental period using oro-gastric cannula. The weight changes and the blood glucose level were observed. Animals were euthanized 24 hour after the last administration and liver was harvested and process for histological observation using H/E and Van Giessen stains. The result shows that the extract of Citrus Medicus caused significant (p-value < 0.05) decrease in blood glucose and increase in the body weight among the animals treated with Citrus Medicus when compared with hyperglycemia untreated group. Histological observation showed hepatic plates that are arranged, with distinct hepatocytes. Hepatic sinusoid are devoid of blood cloths and are well spaced hence, maintanace of hepatic integrity was observed among the animals treated with Citrus Medicus. However, The de- arrangemnt of the hepatic plates, loss of the hepatocytes, loss of hepatic sinusoid and large deposit of the collagen were demonstrated with presences of blood cloths in untreated hyperglycemia animals. Nuclear shrinkages among the array of hepatocytes was equally observed in the hyperglycemia untreated animals. In conclusion, the extract of Citrus Medicus caused reduction in blood sugar, maintenance of body weight and maintenance of histo-hepatic architecture in Alloxan induced diabetic rats.